2017
DOI: 10.3390/ijms18030623
|View full text |Cite
|
Sign up to set email alerts
|

Factors That Negatively Affect the Prognosis of Pediatric Community-Acquired Pneumonia in District Hospital in Tanzania

Abstract: Community-acquired pneumonia (CAP) is still the most important cause of death in countries with scarce resources. All children (33 months ± 35 DS) discharged from the Pediatric Unit of Itigi Hospital, Tanzania, with a diagnosis of CAP from August 2014 to April 2015 were enrolled. Clinical data were gathered. Dried blood spot (DBS) samples for quantitative real-time polymerase chain reaction (PCR) for bacterial detection were collected in all 100 children included. Twenty-four percent of patients were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
18
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 31 publications
(35 reference statements)
6
18
1
2
Order By: Relevance
“…Also, the difference in the deaths of pneumonia in cases who were <2 years of age and the cases who were ≥ 2 years of age was statistically nonsignificant. These results were similar to what was reported by Caggiano S et al (18) who found that co-morbidities did not increase the length of hospitalization and that there were no differences in terms of death and severity of pneumonia between both sexes and among younger and older aged children.…”
Section: Discussionsupporting
confidence: 81%
“…Also, the difference in the deaths of pneumonia in cases who were <2 years of age and the cases who were ≥ 2 years of age was statistically nonsignificant. These results were similar to what was reported by Caggiano S et al (18) who found that co-morbidities did not increase the length of hospitalization and that there were no differences in terms of death and severity of pneumonia between both sexes and among younger and older aged children.…”
Section: Discussionsupporting
confidence: 81%
“…Dried blood spots have been used for bacterial identification and have proven to be a useful and easily accessible tool for molecular diagnosis in poor resources countries [46]. Urinary antigen tests are available for S. pneumoniae and L. pneumophila.…”
Section: Diagnosis Of Capmentioning
confidence: 99%
“…Developing countries are also the most affected due to many additional conditions such as poverty, low economic access to healthcare, lack of appropriate tools for early diagnosis, many socio-cultural barriers, and the unpreparedness against environmental changes. A study from Tanzania has identified the negative role of difficult diagnoses and comorbidities in the prognosis of CAP [46]. Children under 5 years and elderly are the most vulnerable population, and 30-day mortality has not been improved since the 1950s, despite the availability of new antibiotics [47].…”
Section: Cap: Epidemiologymentioning
confidence: 99%
“…Other diseases such as malaria and diarrhea can be important factors that contribute to the susceptibility to pneumonia among children under five in developing countries. A good understanding of risk factors for pneumonia is important to reducing morbidity and mortality rates of pneumonia among children under five (Wojsyk dan Brębo-rowicz, 2013;Roomaney et al, 2016;British Lung Foundation, 2016;Abuka, 2017;Caggiano et al, 2017).…”
mentioning
confidence: 99%